1995
DOI: 10.1149/1.2048547
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer at Photoelectrochemical Solar Cells: Conclusions from the Open‐Circuit Impedance of p ‐ InP in  V 3 +  / 2 +

Abstract: Two resistance-capacitance (RC! time constants are detectable in the open-circuit impedance of illuminated (bare and Ag-treated) p-InP in contact with V 3/2+ + HC1 solution. The dependence of the time constants on illumination intensity and concentration of V 3+ and V 2 § is used to identify processes related to recombination and electrochemical charge transfer, respectively. Charge transfer (CT) rates at metal-treated electrodes [p-InP(Ag)] turn out to be somewhat smaller than at metallic Ag electrodes. For 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…As predicted by the theoretical analysis or model simulation results, the increased with increasing the applied potential bias as indicated in Figure while the arc diameter decreased, which is agreement with the previous reports. …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As predicted by the theoretical analysis or model simulation results, the increased with increasing the applied potential bias as indicated in Figure while the arc diameter decreased, which is agreement with the previous reports. …”
Section: Resultssupporting
confidence: 91%
“…By contrast, electrochemical impedance spectroscopy (EIS) can also be used to obtain the electrode process occurring at illuminated SEI without such a limitation. In fact, by using EIS various equivalent circuit and mathematical models have been proposed to describe the PEC reactions at the illuminated SEI. Surprisingly, little work has been reported on the investigation of the PEC degradation reaction of organic at the TiO 2 /electrolyte solution interfaces by EIS except for Liu's 25 and our reports . Recently, Liu et al have found only one arc on the EIS plane display that had a smaller size corresponding to a faster degradation of sulfosalicylic acid.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the first case, for example, difficulties in finding an adequate theoretical explanation for the frequency dependences were observed. In the second case, the difficulties lie in finding an equivalent circuit whose impedance is the closest to the one measured experimentally [9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…The general EC corresponding to IS, IMPS, and IMVS can be obtained from the analytical models described above, and it is shown in Figure c. We remark that C μ cb has been replaced by a more general capacitance, the outer capacitance of the conduction band C out cb , which accounts for displacement currents such as charging of the Helmholtz layer, typically described as a capacitor C H . It can be noted that light modulation introduces a current source to the classical EC obtained with IS, which arises from the generation term in eq and .…”
mentioning
confidence: 99%